2017
DOI: 10.1002/pssa.201700161
|View full text |Cite
|
Sign up to set email alerts
|

Formation of p‐n Junction in a‐Se Thin Film and Its Application to High Sensitivity Photodetector Driven by Diamond Cold Cathode

Abstract: In this study, photoconductor made of amorphous selenium (a-Se) is studied to improve a sensitivity of vacuum-tube type photodetectors. An electrochemical process was applied to a-Se films to form a p-n structure within the film. The formation of p-n structure was confirmed by time-of-flight secondary ion mass spectroscopy as well as its electronic property. The a-Se film was then combined into a prototype photodetector, and enhancement of sensitivity was evaluated in terms of nominal quantum efficiency and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…23 Furthermore, the high-gain avalanche rushing amorphous photoconductor (HARP) was explored by using an a-Se thin film driven by a diamond cold cathode; however, the detection performance was still very poor and large-area, uniform, and stable emission was difficult to realize with the diamond cold cathode. 43 In addition, the prototype of an X-ray HARP detector using a Spindt-type cold cathode with a pixel number of 640 × 480 and a pixel size of 20 × 20 μm 2 had been reported and was expected to be used in detection for high-throughput protein crystallography. 44 However, Spindt-type cold cathodes are not eligible for large-area detectors, and the amorphous selenium used in the HARP devices is mainly for the low-energy range of ∼20 keV applications due to its relatively low atomic number.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Furthermore, the high-gain avalanche rushing amorphous photoconductor (HARP) was explored by using an a-Se thin film driven by a diamond cold cathode; however, the detection performance was still very poor and large-area, uniform, and stable emission was difficult to realize with the diamond cold cathode. 43 In addition, the prototype of an X-ray HARP detector using a Spindt-type cold cathode with a pixel number of 640 × 480 and a pixel size of 20 × 20 μm 2 had been reported and was expected to be used in detection for high-throughput protein crystallography. 44 However, Spindt-type cold cathodes are not eligible for large-area detectors, and the amorphous selenium used in the HARP devices is mainly for the low-energy range of ∼20 keV applications due to its relatively low atomic number.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The PMT shows the optimal detection performance but is bulky in size and cannot be pixelated. , Miniaturized APD and pixelated SiPM also can realize an excellent photoelectron multiplication using the avalanche effect; however, those devices are unsuitable for large-area imaging due to the silicon-based microfabrication and have the drawback of temperature-dependent gain characteristics. ,, For large-area detection, even though high gain was achieved by a 3D TFT in an active pixel format, the gain dependence on wavelength was still strong and the structures were complicated . Furthermore, the high-gain avalanche rushing amorphous photoconductor (HARP) was explored by using an a-Se thin film driven by a diamond cold cathode; however, the detection performance was still very poor and large-area, uniform, and stable emission was difficult to realize with the diamond cold cathode . In addition, the prototype of an X-ray HARP detector using a Spindt-type cold cathode with a pixel number of 640 × 480 and a pixel size of 20 × 20 μm 2 had been reported and was expected to be used in detection for high-throughput protein crystallography .…”
Section: Resultsmentioning
confidence: 99%
“…As a narrow bandgap semiconductor, Se has a helical chain with weak van der Waals interaction which is considered to have potential applications in high-performance electronic/ optoelectronic devices. [33,59,159,[180][181][182] Ye et al [59] demonstrated that 2D Se nanosheets prepared by vacuum vapor deposition, exhibited excellent p-type transport behaviors with an onstate current density ≈20 mA mm −1 at V ds = 3 V with a high on/off ratio of ≈10 6 . Besides, both the photocurrent (I ph ) and responsivity (R λ ) are linearly proportional to the laser power, indicating that I ph is mainly determined by the photoexcited carriers (Figure 13a,b).…”
Section: Electronics/optoelectronicsmentioning
confidence: 99%